Science, Technology, Engineering and Mathematic (STEM) Education in Malaysia: Preparing the Pre-service Science Teachers - Ahmad Muslihin Ahmad; Nooraida Yakob; Nur Jahan Ahmad (Journal of Natural Science and Integration, 2018)
The aims of this paper is to discuss the importance of science, technology, engineering and mathematic (STEM) education in Malaysian educational system and how it has been implemented in teaching method course.  The policy of STEM education started in the United States and has been expanded to all over the world including Malaysia.  The policy of STEM education in Malaysia has its own understanding based on Malaysian Education policy. In ensuring the successful of STEM education, preservice teachers need to be trained. Hence, School of Educational Studies has taken this initiative to train these student teachers through Chemistry Teaching Methods course.  In this course, student teachers need to plan a lesson plan using 5E instructional model.  They also need to teach based on that lesson plan through simulated teaching in ensuring STEM elements are successfully implemented.